(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
The paper studies the rise of epichoric funerary epigraphy in the Iberian and Celtiberian linguistic areas between the third century BCE and the first century CE in relation to the presence of Roman actors. Despite the difficulties to relate these to and establish a direct causal relation, it shown that the correlation is more than a mere coincidence.